Distinct Vestibular Evoked Myogenic Potentials in Patients With Parkinson Disease and Progressive Supranuclear Palsy - Carpinelli, Sandra; Valko, Philipp O.; Waldvogel, Daniel; Buffone, Elena; Baumann, Christian R.; Straumann, Dominik; Werth, Esther; Bockisch, Christopher J.; Weber, Konrad P.; Valko, Yulia (Frontiers in Neurology, 2021)
Background: Early brainstem neurodegeneration is common in Parkinson’s disease (PD) and progressive supranuclear palsy (PSP). While previous work showed abnormalities in vestibular evoked myogenic potentials (VEMPs) in patients with either disorder as compared to healthy humans, it remains unclear whether ocular and cervical VEMPs differ between PD and PSP patients. Methods: We prospectively included 12 PD and 11 PSP patients, performed ocular and cervical VEMPs, and calculated specific VEMP scores (0=normal, 12=most pathological) based on latencies, amplitude and absent responses. In addition, we assessed disease duration, presence of imbalance, motor asymmetry, and motor disability using the Movement Disorder Society Unified Parkinson's Disease Rating Scale, part III (MDS-UPDRS III). Moreover, we ascertained various sleep parameters by video-polysomnography. Results: PSP and PD patients had similar oVEMP scores (6 [3-6] vs. 3 [1.3-6], p = 0.06), but PSP patients had higher cVEMP scores (3 [0-6] vs. 0 [0-2.8], p = 0.03) and total VEMP scores (9 [5-12] vs. 4 [2-7.5], p = 0.01). Moreover, total VEMP scores >10 were only observed in PSP patients (45%, p=0.01). MDS-UPDRS III correlated with cVEMP scores (rho=0.77, p=0.01) in PSP, but not in PD. In PD, but not in PSP, polysomnographic markers of disturbed sleep, including decreased rapid eye movement sleep, showed significant correlations with VEMP scores. Conclusions: Our findings suggest that central vestibular pathways are more severely damaged in PSP than in PD, as indicated by higher cervical and total VEMP scores in PSP than PD in a between-groups analysis. Meaningful correlations between VEMPs and motor and non-motor symptoms further encourage its use in neurodegenerative Parkinsonian syndromes.